Finding female identity in the Neo-Confucian country of Joseon: analysis of female-related crimes in “Sabeobpumbo” (司法稟報) - Han, Boram (International Journal of Korean Humanities and Social Sciences, 2022)
This research analyzes female-related cases in Sabeobpumbo (사법품보, 司法稟報) to examine Joseon women’s identity and perceptions of their role in the patriarchal society. Since women’s chastity was directly related to their social value, it was sometimes traded for their lives. Women were often unfairly reprehended when involved in domestic conflicts because of their lower status and they have been understood as individuals who faithfully followed the agnatic principle. However, there were exceptions, and Sabeobpumbo contained extraordinary accounts of various Joseon women in which they were described as independent and displayed active defiance in response to their highly conservative society while hoping to break free from the rigid social structure. In some cases, Joseon women decisively left their husbands for various reasons, mostly involving financial instability or neglecting duties. Furthermore, some women went to incredible lengths to preserve their husband’s and his family’s dignity. Interestingly enough, these women were not only absolved from their actions but even met with silent approval from the public. These examples provide an intriguing perspective that directly clashes with the accepted norms during the Joseon Dynasty and calls for further research on the complexities of female identity as a Joseon woman.